Adaptasi praktik literasi informasi mahasiswa di era kecerdasan buatan dalam perspektif humaniora digital - Fakhlina, Resty Jayanti; Arwendria, Arwendria; Sari, Shinta Nofita; Rahmi, Lailatur; Zalmi, Fadhila Nurul Husna; Bifakhlina, Febriyanti (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. Digital transformation accelerated by advances in artificial intelligence (AI) has changed the way students explore and evaluate information, especially in the early stages of digital literacy. This study aims to analyse the information literacy practices of students of the Faculty of Adab and Humanities (FAH) and the Faculty of Science and Technology (FST) of UIN Imam Bonjol Padang in the context of Digital Humanities, focusing on the use of AI-based tools in the search, discovery and evaluation of information sources. Methodology. This research uses a quantitative approach with a descriptive-comparative design. The sample consisted of 245 FAH and FST students of UIN Imam Bonjol Padang, who were purposively selected. Data were collected through a five-point Likert questionnaire and analysed using SPSS version 26 with descriptive and Chi-Square tests. The validity and reliability of the instruments were tested, with Cronbach's Alpha >0.80. Results and discussion. The findings indicate that the majority of respondents routinely use AI tools such as ChatGPT, Google Bard, Gemini, and Perplexity for initiating information searches. AI is considered highly useful for initial reference discovery, expanding exploration scopes, and distinguishing between relevant and irrelevant sources. However, doubts remain among students regarding AI's effectiveness in assessing source credibility. These results underscore the need to integrate critical thinking approaches into AI-based digital literacy education in Islamic higher education institutions. Conclusions. This study contributes to the Digital Humanities discourse by offering an initial mapping of students' interaction patterns with AI in the digital information literacy landscape.